2015
DOI: 10.1371/journal.pone.0116477
|View full text |Cite
|
Sign up to set email alerts
|

Use of Genome-Wide Association Studies for Cancer Research and Drug Repositioning

Abstract: Although genome-wide association studies have identified many risk loci associated with colorectal cancer, the molecular basis of these associations are still unclear. We aimed to infer biological insights and highlight candidate genes of interest within GWAS risk loci. We used an in silico pipeline based on functional annotation, quantitative trait loci mapping of cis-acting gene, PubMed text-mining, protein-protein interaction studies, genetic overlaps with cancer somatic mutations and knockout mouse phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Researchers are now developing approaches that analyze genetic associations in the context of networks and pathways to prioritize potential drugs (16)(17)(18)(19)(20)(21). There is not yet a standard approach or set of techniques that are widely applied, so we highlight examples of the types of techniques being employed.…”
Section: Pathway and Network-based Drug Identification From Genetic Amentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are now developing approaches that analyze genetic associations in the context of networks and pathways to prioritize potential drugs (16)(17)(18)(19)(20)(21). There is not yet a standard approach or set of techniques that are widely applied, so we highlight examples of the types of techniques being employed.…”
Section: Pathway and Network-based Drug Identification From Genetic Amentioning
confidence: 99%
“…Overlaying drug-target information from DrugBank (23) and the Therapeutic Targets Database (23) revealed that a number of top candidates from the analysis were already targets of existing drugs for RA, suggesting that drugs targeting other top candidates might also be repurposed to treat RA. A similar approach has also been used to identify anti-cancer drugs (21).…”
Section: Pathway and Network-based Drug Identification From Genetic Amentioning
confidence: 99%
“…Similar efforts to systematically translate results from large-scale GWAS studies into drug repurposing hypotheses have been previously published 9,[13][14] . It may be useful to compare these different workflows to predict drug candidates from GWAS data in future studies.…”
mentioning
confidence: 90%
“…The overall goal of this method is to systematically integrate diverse types of drug, genetic and clinical data to enable drug repurposing for users from diverse communities, including clinical, industry and regulatory communities. The foundational methods for this system have been previously reported for the use of genomewide association study (GWAS) and phenome-wide association study (PheWAS) data in drug repurposing research 9,10 . The novel combination of these types of data distinguishes our webtool from other target-based methods 6,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the underlying mechanisms may be complex and even seem contradictory at times, these examples all highlight the potential for breast cancer GWAS to find important and novel breast cancer genes, with the ultimate aim of developing new therapeutics or biomarkers of disease [26]. From a clinical perspective however, even without extensive fine mapping and any mechanistic understanding of the causal SNP effects, GWAS data can be used to guide the repositioning of existing drugs which target genes within the identified risk locus [446,447].…”
Section: Final Discussionmentioning
confidence: 99%